Pengembangan Komposit Berbahan Dasar Glycerin Pitch untuk Pembuatan BioPlafon Ramah Lingkungan - Fadlin Qisthi Nasution; M. Ansori Nasution; Meta Rivani; Mhd. Erlangga Habibi Nasution; Rivaldy Yustianto Pasaribu; Arjanggi Nasution; M. Anshari (Prosiding Seminar Nasional Teknoka, 2025)
The development and mechanical performance of sand–fly ash composites utilizing glycerin pitch, a biodiesel residue, as a bio-based binder were investigated. Experimental variables included glycerin pitch concentration (10–25% v/v), sand-to-fly ash ratio (35:65–65:35), curing temperature (190–350°C), and curing time (4–24 h). The optimal flexural strength of 1.82 MPa was obtained with 15% v/v glycerin pitch, a 42:58 sand-to-fly ash ratio,  and curing at 190°C for 24 hours. Binder concentrations exceeding 15% or curing temperatures above 250°C resulted in disintegration or carbonization, indicating binder degradation. The produced composite demonstrated adequate strength and stability for non-load-bearing applications, including sustainable ceiling panels and interior partitions. These results demonstrate the potential of glycerin pitch as a renewable binder for transforming industrial residues into eco-efficient building materials and advancing circular economy practices in construction.